Anti-corrosion electromagnetic shielding coating as well as preparation method and application thereof
By preparing a magnetic-conductive layer on the conductive layer, the synergistic effect of the conductive layer and the magnetic-conductive layer is solved, and the existing corrosion-resistant electromagnetic shielding coatings have low shielding efficiency and short corrosion resistance life are achieved, achieving efficient and economical electromagnetic shielding effect.
Patent Information
- Application Number
- CN202411925260.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing corrosion-resistant electromagnetic shielding coatings have low shielding performance and short corrosion resistance life, making it difficult to meet the requirements of long-term service in corrosive environments such as the ocean.
By preparing a magnetically conductive layer on the conductive layer, the thickness of the conductive layer is smaller than the thickness of the magnetically conductive layer, and the synergistic effect of the conductive layer on the reflection attenuation of the electromagnetic wave and the absorption loss of the magnetically conductive layer on the electromagnetic wave is achieved.
The electromagnetic shielding efficiency of 100MHz~18GHz after 3000h acid salt spray is achieved, and the production cost is reduced, with lower cost, higher shielding efficiency and better corrosion resistance.
Smart Images

Figure CN119570336A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electromagnetic shielding, and in particular to an anti-corrosion electromagnetic shielding coating and a preparation method and application thereof. Background Art
[0002] With the continuous innovation and development of modern industrial technology, in the field of electronic information industry, various types of communication equipment and electronic products are increasing rapidly and becoming more and more popular. At the same time, the rapid development of electronic equipment has enabled my country's modern national defense to reach an unprecedented level. However, electronic and electrical equipment are very likely to generate electromagnetic radiation and be susceptible to electromagnetic interference from the outside world while working, thus causing electromagnetic wave pollution in the air and causing serious interference to the normal operation of electronic and electrical equipment, especially the electromagnetic interference from the outside world to electronic and electrical equipment, which can cause equipment damage and personal injury in severe cases, causing serious economic losses to business and national defense. Therefore, certain protective measures must be taken, and a functional electromagnetic shielding coating is usually applied to the surface of electronic and electrical equipment.
[0003] The electromagnetic shielding coating after the electromagnetic shielding coating is completely film-formed and cured can block the transmission route of external electromagnetic waves, making it difficult for electromagnetic waves to enter the interior of electronic and electrical equipment, thereby protecting precision equipment. The electromagnetic shielding coating is composed of film-forming resin, shielding agent, curing agent, dispersant, anti-settling agent and solvent. Among them, the electromagnetic properties of the shielding agent are the key to determining the shielding effect of the electromagnetic shielding coating. To obtain electromagnetic shielding coatings with high shielding efficiency, it is necessary to add a large dose of conductive filler to the coating. This will make the highly active conductive filler more easily exposed to corrosive media. Therefore, it is difficult to take into account both the high shielding efficiency and corrosion resistance of electromagnetic shielding coatings. Gui Taijiang from the Marine Chemical Industry Research Institute [1] et al. invented a corrosion-resistant electromagnetic shielding coating, but its shielding effectiveness in the range of 1MHz~1GHz is only 26~68dB, and the stability of the coating can only be guaranteed after 144h neutral salt spray and 120h wet heat test. Zheng Kai et al. from China Electronics Technology Group Corporation 33rd Institute invented a corrosion-resistant electromagnetic shielding coating for aluminum alloy surfaces, which can maintain stable properties after 528h neutral salt spray test. However, these corrosion-resistant electromagnetic shielding coatings have low shielding effectiveness and short corrosion resistance life, which makes it difficult to meet the requirements of long-term service in corrosive environments such as the ocean. Therefore, it is urgent to develop a low-cost, corrosion-resistant, high-performance electromagnetic shielding coating. Summary of the invention
[0004] In view of the deficiencies in the above-mentioned background technology, the present invention mainly solves the problems that the shielding effectiveness of corrosion-resistant electromagnetic shielding coatings in the prior art is low, and the corrosion resistance life is short, which makes it difficult to meet the requirements of long-term service in corrosive environments such as the ocean. The present invention provides an anti-corrosion electromagnetic shielding coating and its preparation method and application. The coating achieves the shielding effect of electromagnetic waves by preparing a magnetic conductive layer on a conductive layer, and the thickness of the conductive layer is less than that of the magnetic conductive layer, and utilizing the synergistic effect of the reflection attenuation of the conductive layer on the electromagnetic waves and the absorption loss of the magnetic conductive layer on the electromagnetic waves.
[0005] The first object of the present invention is to provide an anti-corrosion electromagnetic shielding coating, the coating comprising a conductive layer and a magnetic conductive layer, wherein the magnetic conductive layer is located on the conductive layer; The conductive layer is formed by curing a conductive coating, wherein the conductive coating comprises the following components in parts by weight: 35-50 parts of a resin, 3-15 parts of a curing agent, 20-120 parts of a conductive filler, 1-2 parts of a dispersant, 1-2 parts of an anti-settling agent, and 10-75 parts of a solvent; The magnetic conductive layer is formed by curing the magnetic conductive coating, and the magnetic conductive coating comprises the following components in parts by weight: 35-50 parts of resin, 3-15 parts of curing agent, 20-120 parts of magnetic conductive filler, 1-2 parts of dispersant, 1-2 parts of anti-settling agent, and 10-75 parts of solvent; The conductive filler is one or more of gold powder, silver powder, silver-coated aluminum powder, nickel-coated graphite powder, silver-coated copper powder, carbon black, carbon nanotubes, and carbon fibers; The magnetic conductive filler is flaky nickel powder.
[0006] Preferably, the flaky nickel powder is prepared according to the following steps: adding spherical nickel powder, zirconium oxide grinding balls and anhydrous ethanol to a ball mill in proportion, setting the ball milling speed and ball milling time, filtering after the ball milling operation is completed, and drying at 75-85° C. to obtain the flaky nickel powder.
[0007] Preferably, the particle size of the spherical nickel powder is 3~15μm; the mass ratio of the spherical nickel powder to the zirconium oxide grinding ball is 1:3~15, and the mass ratio of the spherical nickel powder to the anhydrous ethanol is 1:1~3; the ball milling speed is 100~300r / min, and the ball milling time is 5~20h.
[0008] Preferably, the thickness of the conductive layer is 20-100 μm; the thickness of the magnetic conductive layer is 200-1000 μm.
[0009] Preferably, the resin is one or more of silicone resin, epoxy resin, acrylic resin and polyurethane resin.
[0010] Preferably, the curing agent is selected from one or more of polyamide, polyetheramine, and fatty amine; The dispersant is DISPERBYK-110 dispersant; The anti-settling agent is selected from paraffin and / or organic bentonite.
[0011] Preferably, the solvent is selected from one or more of toluene, xylene, acetone, butanone, isopropanol, propylene glycol methyl ether acetate, and n-butanol.
[0012] The second object of the present invention is to provide a method for preparing an anti-corrosion electromagnetic shielding coating, which is characterized by comprising the following steps: Weigh the resin, curing agent, conductive filler, dispersant, anti-settling agent and solvent by weight, mix the weighed raw materials of each component, and stir them evenly using a homogenizer to obtain the conductive coating; Weigh the resin, curing agent, magnetic conductive filler, dispersant, anti-settling agent and solvent according to weight, mix the weighed raw materials of each component, and stir them evenly using a homogenizer to obtain the magnetic conductive coating; The conductive coating is applied on the surface of the substrate by air spraying, and heated and cured to prepare the conductive layer; The magnetic conductive coating is coated on the surface of the conductive layer by air spraying, and heated and cured to prepare the magnetic conductive layer.
[0013] Preferably, the stirring speed of the homogenizer is 500-3000 r / min, and the stirring time is 5-20 min; The process parameters of the air spraying method are: spraying pressure 0.2~0.8MPa, spraying distance 10~60cm, spraying angle 80~100°, spray gun moving speed 15~45cm / s; The process parameters of the heating and heat preservation are: curing temperature 60-120° C., and curing time 6-12 hours.
[0014] The third object of the present invention is to provide an anti-corrosion electromagnetic shielding coating for use in electromagnetic shielding.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides an anti-corrosion electromagnetic shielding coating and a preparation method and application thereof. The present invention prepares a magnetic conductive layer on a conductive layer, and the thickness of the conductive layer is less than that of the magnetic conductive layer, and utilizes the synergistic effect of the reflection attenuation of the conductive layer on the electromagnetic wave and the absorption loss of the magnetic conductive layer on the electromagnetic wave to achieve the shielding effect of the electromagnetic wave. In addition, see Figure 2As shown, on the one hand, the magnetic conductive layer uses flaky fillers as fillers, which can significantly extend the propagation path of the corrosive medium inside the magnetic conductive layer; on the other hand, the standard electrode potential (-0.23V) of the magnetic conductive layer filler is much lower than the standard electrode potential (0.337~3.7V) of the conductive layer. When the corrosive medium invades the coating, the magnetic conductive filler can act as an anode sacrifice to protect the conductive layer, thereby ensuring the shielding effectiveness of the coating after corrosion to the greatest extent. Compared with the pure conductive layer shielding coating, this double coating structure material can ensure that the electromagnetic shielding effectiveness of 100MHz~18GHz is greater than 60dB after 3000h of acid salt spray while reducing the production cost. Compared with the existing electromagnetic shielding coating materials, the electromagnetic shielding coating material provided by the present invention has the advantages of lower cost, higher shielding effectiveness, better corrosion resistance, etc. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 Schematic diagram of the structure of the anti-corrosion electromagnetic shielding coating.
[0016] Figure 2 Schematic diagram of extending the corrosion path for the magnetic conductive layer.
[0017] Figure 3 This is a scanning electron microscope image of the homemade flaky nickel powder in Example 5.
[0018] Figure 4 These are surface photographs of Example 1, Comparative Example 1 and Comparative Example 2 after 3000 hours of acid salt spray corrosion.
[0019] Among them, 1 is a conductive layer, and 2 is a magnetic conductive layer. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.
[0021] The purpose of the present invention is to provide an anti-corrosion electromagnetic shielding coating and a preparation method and application thereof.
[0022] To achieve the above purpose, see Figure 1 As shown, an anti-corrosion electromagnetic shielding coating comprises a conductive layer 1 and a magnetic conductive layer 2, wherein the magnetic conductive layer 2 is located on the conductive layer 1; The thickness of the conductive layer 1 is 20-100 μm; the thickness of the magnetic conductive layer 2 is 200-1000 μm.
[0023] The conductive layer 1 is formed by curing a conductive coating, wherein the conductive coating comprises the following components in parts by weight: 35-50 parts of resin, 3-15 parts of curing agent, 20-120 parts of conductive filler, 1-2 parts of dispersant, 1-2 parts of anti-settling agent, and 10-75 parts of solvent; The magnetic conductive layer 2 is formed by curing the magnetic conductive coating, wherein the magnetic conductive coating comprises the following components in parts by weight: 35-50 parts of resin, 3-15 parts of curing agent, 20-120 parts of magnetic conductive filler, 1-2 parts of dispersant, 1-2 parts of anti-settling agent, and 10-75 parts of solvent.
[0024] The conductive filler and magnetic conductive filler used in the present invention have good magnetic permeability and electrical conductivity to ensure the shielding effectiveness of the electromagnetic shielding coating; the resin selected in the present invention has excellent wettability to the above-mentioned types of electromagnetic shielding fillers, and the resin can spread on the surface of the electromagnetic shielding filler very well during the coating curing process to form a very thin nano resin layer, which not only ensures the mutual adhesion between the electromagnetic shielding fillers, but also allows the electromagnetic shielding filler particles to form a conductive circuit or a magnetic conductive circuit through the tunnel effect or magnetic exchange effect; the curing agent has good offensive activity, can reduce the curing temperature of the resin, accelerate the curing of the resin, and increase the crosslinking density of the resin. The dispersant and the anti-settling agent can promote the uniform distribution of the electromagnetic shielding filler inside the resin through electrostatic action and steric hindrance, and further improve the wetting of the resin on the electromagnetic shielding filler. The solvent can dilute the coating, ensure the processability of the coating, and realize the directional distribution of the electromagnetic shielding filler inside the coating by improving the rheological properties of the coating, further increase the electrical conductivity and magnetic permeability of the coating, thereby improving the shielding effectiveness of the coating.
[0025] The conductive filler is one or more of gold powder, silver powder, silver-coated aluminum powder, nickel-coated graphite powder, silver-coated copper powder, carbon black, carbon nanotubes, and carbon fibers; the gold powder is a dark gold powder with a particle size of 10 to 15 μm; the silver powder is a dark silver powder with a D50 of 7 μm; the aluminum powder is a bright silver powder with a D50 of 15 μm; the carbon black is a nanoscale black powder; the carbon nanotube is a black powder with a diameter of about 15 nm and an aspect ratio of about 1000; the carbon fiber is a black fibrous solid with a length of about 1.5 mm. The conductive filler is a product of Shaanxi General Nanotechnology Co., Ltd.
[0026] The magnetic conductive filler is flaky nickel powder.
[0027] The flaky nickel powder is prepared according to the following steps: adding spherical nickel powder, zirconium oxide grinding balls and anhydrous ethanol to a ball mill in proportion, setting the ball milling speed and ball milling time, filtering after the ball milling operation is completed, and drying at 75-85° C. to obtain the flaky nickel powder, whose D50 is ~37 μm.
[0028] In one embodiment, the preparation steps of the flaky nickel powder are as follows: spherical nickel powder, zirconium oxide grinding balls and anhydrous ethanol are added to a ball mill in a mass ratio of 1:3~15:1~3, the ball mill speed is set to 100~300r / min at room temperature, the ball milling time is 5~20h, after the ball milling operation is completed, filtering and drying to obtain the flaky nickel powder magnetic filler, wherein the SEM image of the flaky nickel powder used in Example 5 is as shown in FIG. Figure 3 shown.
[0029] The particle size of the spherical nickel powder is 3-15 μm; the mass ratio of the spherical nickel powder to the zirconium oxide grinding ball is 1:3-15, and the mass ratio of the spherical nickel powder to the anhydrous ethanol is 1:1-3; the ball milling speed is 100-300 r / min, and the ball milling time is 5-20 h.
[0030] The resin is one or more of silicone resin, epoxy resin, acrylic resin and polyurethane resin, all of which are products of Hubei Xinsihai Chemical Co., Ltd.
[0031] The curing agent is selected from one or more of polyamide, polyetheramine and fatty amine; polyamide is a medium-viscosity brown-yellow liquid, polyetheramine is a low-viscosity light yellow liquid, and fatty amine is a medium-viscosity transparent liquid, all of which are products of Hubei Xinsihai Chemical Co., Ltd.
[0032] The dispersant is DISPERBYK-110 dispersant; the dispersant is an oily liquid dispersant, and is a product of Shenzhen Pasto Chemical Co., Ltd.
[0033] The anti-settling agent is selected from paraffin and / or organic bentonite, both of which are products of Hubei Xinsihai Chemical Co., Ltd. The paraffin anti-settling agent is a milky white paste, and the organic bentonite is a white or light yellow powder.
[0034] The solvent is selected from one or more of toluene, xylene, acetone, butanone, isopropanol, propylene glycol methyl ether acetate, and n-butanol, and is a product of Nanjing Hecheng Chemical Co., Ltd. Toluene is a colorless, volatile liquid with a special aromatic smell, xylene is a colorless transparent liquid with a special aromatic smell, acetone is a colorless flammable liquid with a mint smell, butanone is a colorless transparent liquid with a mint-like smell, isopropanol is a colorless transparent liquid with an odor similar to a mixture of ethanol and acetone, propylene glycol methyl ether acetate is a colorless hygroscopic liquid with a special smell, and n-butanol is a colorless transparent liquid with a wine smell. A second aspect of the present invention provides a method for preparing an anti-corrosion electromagnetic shielding coating, comprising the following steps: Weigh the resin, curing agent, conductive filler, dispersant, anti-settling agent and solvent by weight, mix the weighed raw materials of each component, and stir them evenly using a homogenizer to obtain the conductive coating; Weigh the resin, curing agent, magnetic conductive filler, dispersant, anti-settling agent and solvent according to weight, mix the weighed raw materials of each component, and stir them evenly using a homogenizer to obtain the magnetic conductive coating; The conductive coating is coated on the surface of the substrate by air spraying, and heated and cured to prepare the conductive layer. The specific process is as follows: The conductive coating is loaded into a spraying device, and sprayed evenly on the surface of the substrate in an S-shaped path, with a single-pass spraying thickness of less than 30 μm. After each 0.1 mm coating is sprayed, the sample is dried at room temperature for 10 to 15 minutes, and then the sample is placed in an oven for heating and heat preservation to solidify the conductive coating sprayed on the surface of the substrate to obtain a first conductive prefabricated layer; the preparation process of the first conductive prefabricated layer is repeated until the thickness of the obtained conductive prefabricated layer reaches the designed thickness to obtain a conductive layer; The magnetic conductive coating is coated on the surface of the conductive layer by air spraying, and heated and cured to prepare the magnetic conductive layer. The specific process is as follows: The magnetic conductive coating is loaded into a spraying device and sprayed evenly on the surface of the conductive layer in an S-shaped path, with a spraying thickness of less than 30 μm; after each 0.1 mm coating is sprayed, the sample is dried at room temperature for 10 to 15 minutes, and then the sample is placed in an oven for heating and insulation to solidify the magnetic conductive coating sprayed on the surface of the conductive layer to obtain a first magnetic conductive prefabricated layer; the preparation process of the first magnetic conductive prefabricated layer is repeated until the thickness of the obtained magnetic conductive prefabricated layer reaches the designed thickness to obtain a magnetic conductive layer; that is, the anti-corrosion electromagnetic shielding coating is obtained.
[0035] Wherein, the stirring speed of the homogenizer is 500~3000r / min, and the stirring time is 5~20min; The process parameters of the air spraying method are: spraying pressure 0.2~0.8MPa, spraying distance 10~60cm, spraying angle 80~100°, spray gun moving speed 15~45cm / s; The process parameters of the heating and heat preservation are: curing temperature 60-120° C., and curing time 6-12 hours.
[0036] The third aspect of the present invention provides an application of an anti-corrosion electromagnetic shielding coating in electromagnetic shielding It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.
[0037] Example Step 1. Preparation of substrate An epoxy plastic plate with a thickness of 0.5 mm was used as the substrate, and the surface of the substrate was cleaned with anhydrous ethanol to ensure that there were no dust particles on the surface of the substrate.
[0038] Step 2. Prepare the coating Step 2.1 Conductive coating preparation Resin, curing agent, conductive filler, dispersant, anti-settling agent and solvent are weighed in parts by weight, the weighed raw materials of each component are mixed, and stirred evenly using a homogenizer to obtain a conductive coating.
[0039] Among them, the stirring speed of the homogenizer is 500~3000r / min, and the stirring time is 5~20min.
[0040] Step 2.2 Preparation of magnetic conductive coating Resin, curing agent, magnetic conductive filler, dispersant, anti-settling agent and solvent are weighed in parts by weight, the weighed raw materials of each component are mixed, and stirred evenly by a homogenizer to obtain a magnetic conductive coating.
[0041] Among them, the stirring speed of the homogenizer is 500~3000r / min, and the stirring time is 5~20min.
[0042] Step 3. Prepare the conductive layer The conductive coating is applied on the surface of the substrate by air spraying, and heated and cured to prepare a conductive layer; The specific process is as follows: load the conductive coating into the spraying device and spray it evenly on the surface of the substrate in an S-shaped path, with a spraying thickness of less than 30 μm; dry the sample at room temperature for 10 to 15 minutes after each 0.1 mm coating is sprayed, and then place the sample in an oven and keep it at 60 to 120°C for 6 to 12 hours to solidify the conductive coating sprayed on the surface of the substrate to obtain the first conductive prefabricated layer; repeat the preparation process of the first conductive prefabricated layer until the thickness of the conductive prefabricated layer reaches the designed thickness to obtain a conductive layer.
[0043] Among them, the process parameters of the air spray method are: spraying pressure 0.2~0.8MPa, spraying distance 10~60cm, spraying angle 80~100°, and spray gun moving speed 15~45cm / s.
[0044] Step 4. Prepare the magnetic conductive layer The magnetic conductive coating is coated on the surface of the conductive layer by air spraying, and heated and cured to prepare the magnetic conductive layer; The specific process is: load the magnetic conductive coating into the spraying device, and spray it evenly on the surface of the conductive layer in an S-shaped path, with a spraying thickness of less than 30μm; after each 0.1mm coating is sprayed, the sample is dried at room temperature for 10~15min, and then the sample is placed in an oven and kept warm at 60~100℃ for 8~12h to solidify the magnetic conductive coating sprayed on the surface of the conductive layer to obtain the first magnetic conductive prefabricated layer; repeat the preparation process of the first magnetic conductive prefabricated layer until the thickness of the obtained magnetic conductive prefabricated layer reaches the designed thickness to obtain a magnetic conductive layer; that is, an anti-corrosion electromagnetic shielding coating is obtained.
[0045] Among them, the process parameters of the air spray method are: spraying pressure is 0.2~0.8MPa, spraying distance is 10~60cm, spraying angle is 80~100°, and spray gun moving speed is 15~45cm / s.
[0046] The process parameters of the magnetic conductive filler in each embodiment are shown in Table 1.
[0047] Table 1 Process parameters of magnetic conductive fillers in various embodiments
[0048] The composition of the anti-corrosion electromagnetic shielding coating in each embodiment is shown in Table 2.
[0049] Table 2 Composition of the anti-corrosion electromagnetic shielding coating in each embodiment
[0050] The process parameters of each embodiment are shown in Table 3.
[0051] Table 3 Process parameters of each embodiment
[0052] Comparative Example 1 An electromagnetic shielding coating includes only a magnetic conductive layer. The preparation method of the magnetic conductive layer filler is the same as that shown in Example 1 in Table 1, specifically: 1 kg of nickel powder, 3 kg of zirconium oxide ball milling beads, and 1 kg of anhydrous ethanol are added to a stirring ball mill, ball milled at 100 rpm for 5 hours, filtered, and dried at 80°C to obtain a flaky nickel powder magnetic conductive filler. 35 parts of epoxy resin, 3 parts of polyamide, 20 parts of flaky nickel powder magnetic conductive fillers, 1 part of DISPERBYK-110, 1 part of organic bentonite, 7 parts of xylene, 5 parts of propylene glycol methyl ether acetate, and 3 parts of n-butanol are prepared into a magnetic conductive coating according to the method described above, and a coating with a thickness of 220 μm is prepared using the process parameters of Example 1 in Table 3.
[0053] Comparative Example 2 An electromagnetic shielding coating includes only a conductive layer, and the conductive layer is prepared by: 35 parts of silicone resin, 3 parts of polyamide, 60 parts of silver powder, 1 part of DISPERBYK-110, 1 part of organic bentonite, 7 parts of xylene, 5 parts of propylene glycol methyl ether acetate, and 3 parts of n-butanol were prepared into a conductive coating according to the method described above, and a coating with a thickness of 220 μm was prepared using the process parameters of Example 1 in Table 3.
[0054] In order to illustrate the microscopic morphology of the flaky nickel powder prepared in the embodiment of the present invention, the morphology of the flaky nickel powder was observed using a TESCAN Vega 3 scanning electron microscope in accordance with JY / T 0584-2020 "General Rules for Scanning Electron Microscope Analysis Methods". The results are as follows Figure 3 As shown in the figure, it can be seen that the nickel flakes have a high degree of flake formation, a large diameter-to-thickness ratio, and no breakage due to stress.
[0055] In order to illustrate the corrosion resistance and electromagnetic shielding effectiveness of the anti-corrosion electromagnetic shielding coating prepared in the embodiment of the present invention, the corrosion resistance and electromagnetic shielding effectiveness of the prepared anti-corrosion electromagnetic shielding coating were tested according to GJB150.11A-2009 "Laboratory Environmental Test Method for Military Equipment" and GJB 8820-2015 "Measurement Method for Shielding Effectiveness of Electromagnetic Shielding Materials", and the test results are shown in Tables 4 and 5.
[0056] Table 4 Acid salt spray resistance test results of each embodiment
[0057] It can be seen from Table 4 that in the acidic salt spray environment experiment, the anti-corrosion electromagnetic shielding coating prepared in the embodiment of the present invention has no peeling, blistering, wrinkling, cracking or falling off on the surface of the coating, indicating that the prepared anti-corrosion electromagnetic shielding coating has excellent corrosion resistance.
[0058] Table 5 Electromagnetic shielding effectiveness test results of various embodiments
[0059] It can be seen from Table 5 that the anti-corrosion electromagnetic shielding coating prepared in the embodiment of the present invention has excellent shielding effect on electromagnetic waves in the 100MHz~18GHz band, and its electromagnetic shielding effectiveness value is higher than 60dB and reaches the military level, meeting the shielding requirements in special fields.
[0060] Table 6 Electromagnetic shielding effectiveness test results of each embodiment and comparative example before and after 3000h salt spray
[0061] As can be seen from Table 6, the electrical conductivity and magnetic permeability of Comparative Example 1 (only the magnetic conductive layer) are low, and the shielding effectiveness is much lower than that of Example 1. Comparative Example 2 (only the conductive layer) has good electrical conductivity and high shielding effectiveness before corrosion, but the shielding effectiveness decays rapidly after 3000h of acid salt spray, and the shielding effectiveness is less than 60dB in the range of 100MHz~18GHz. For Example 1, its shielding effectiveness in the range of 100MHz~18GHz before and after corrosion is greater than 60dB. The surface photos of Example 1 and Comparative Examples 1 and 2 after 3000h of acid salt spray corrosion are shown in Figure 6. Figure 4 As shown. It can be seen that thanks to the excellent absorption loss and anti-corrosion effect of the magnetic conductive layer, the anti-corrosion electromagnetic shielding coating of the present invention not only has excellent shielding effectiveness, but also has good corrosion resistance.
[0062] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An anti-corrosion electromagnetic shielding coating, characterized in that: The coating comprises a conductive layer and a magnetic conductive layer, wherein the magnetic conductive layer is located on the conductive layer; The conductive layer is formed by curing a conductive coating, wherein the conductive coating comprises the following components in parts by weight: 35-50 parts of a resin, 3-15 parts of a curing agent, 20-120 parts of a conductive filler, 1-2 parts of a dispersant, 1-2 parts of an anti-settling agent, and 10-75 parts of a solvent; The magnetic conductive layer is formed by curing the magnetic conductive coating, and the magnetic conductive coating comprises the following components in parts by weight: 35-50 parts of resin, 3-15 parts of curing agent, 20-120 parts of magnetic conductive filler, 1-2 parts of dispersant, 1-2 parts of anti-settling agent, and 10-75 parts of solvent; The conductive filler is one or more of gold powder, silver powder, silver-coated aluminum powder, nickel-coated graphite powder, silver-coated copper powder, carbon black, carbon nanotubes, and carbon fibers; The magnetic conductive filler is flaky nickel powder.
2. The anti-corrosion electromagnetic shielding coating according to claim 1, characterized in that: The flaky nickel powder is prepared according to the following steps: adding spherical nickel powder, zirconium oxide grinding balls and anhydrous ethanol to a ball mill in proportion, setting the ball milling speed and ball milling time, filtering after the ball milling operation is completed, and drying at 75-85° C. to obtain the flaky nickel powder.
3. The anti-corrosion electromagnetic shielding coating according to claim 2, characterized in that: The particle size of the spherical nickel powder is 3-15 μm; the mass ratio of the spherical nickel powder to the zirconium oxide grinding ball is 1:3-15, and the mass ratio of the spherical nickel powder to the anhydrous ethanol is 1:1-3; the ball milling speed is 100-300 r / min, and the ball milling time is 5-20 h.
4. The anti-corrosion electromagnetic shielding coating according to claim 1, characterized in that: The thickness of the conductive layer is 20-100 μm; the thickness of the magnetic conductive layer is 200-1000 μm.
5. The anti-corrosion electromagnetic shielding coating according to claim 1, characterized in that: The resin is one or more of silicone resin, epoxy resin, acrylic resin and polyurethane resin.
6. The anti-corrosion electromagnetic shielding coating according to claim 1, characterized in that: The curing agent is selected from one or more of polyamide, polyetheramine and fatty amine; The dispersant is DISPERBYK-110 dispersant; The anti-settling agent is selected from paraffin and / or organic bentonite.
7. The anti-corrosion electromagnetic shielding coating according to claim 1, characterized in that: The solvent is selected from one or more of toluene, xylene, acetone, butanone, isopropanol, propylene glycol methyl ether acetate, and n-butanol.
8. A method for preparing the anti-corrosion electromagnetic shielding coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: Weigh the resin, curing agent, conductive filler, dispersant, anti-settling agent and solvent by weight, mix the weighed raw materials of each component, and stir them evenly using a homogenizer to obtain the conductive coating; Weigh the resin, curing agent, magnetic conductive filler, dispersant, anti-settling agent and solvent according to weight, mix the weighed raw materials of each component, and stir them evenly using a homogenizer to obtain the magnetic conductive coating; The conductive coating is applied on the surface of the substrate by air spraying, and heated and cured to prepare the conductive layer; The magnetic conductive coating is coated on the surface of the conductive layer by air spraying, and heated and cured to prepare the magnetic conductive layer.
9. The method for preparing the anti-corrosion electromagnetic shielding coating according to claim 8, characterized in that: The stirring speed of the homogenizer is 500-3000 r / min, and the stirring time is 5-20 min; The process parameters of the air spraying method are: spraying pressure 0.2~0.8MPa, spraying distance 10~60cm, spraying angle 80~100°, spray gun moving speed 15~45cm / s; The process parameters of the heating and heat preservation are: curing temperature 60-120° C., and curing time 6-12 hours.
10. Use of the anti-corrosion electromagnetic shielding coating according to any one of claims 1 to 7 in electromagnetic shielding.
Citation Information
Patent Citations
Composite coating electromagnetic shielding paint and composite coating electromagnetic shielding material prepared therefrom
CN102020899A
Polymer-based electromagnetic shielding composite material with sandwich structure and preparation method thereof
CN107216587A
Multi-layer coating
CN115678422A
Low-frequency shielding coating and preparation method thereof
CN115717017A
Anti-corrosion transparent electromagnetic shielding film and preparation method and application thereof
CN117979673A